Nomenclatural notes on Myristica yunnanensis and Cyclobalanopsis yonganensis - Peng, Xiao-Ming; He, Zheng; Yu, Wen-Bin (Bangladesh Journal of Plant Taxonomy, 2011)
Not available Keywords: Myristica yunnanensis; Myristicaceae; Cyclobalanopsis yonganensis; Fagaceae; Publication date; Nomenclature. DOI: 10.3329/bjpt.v18i1.7840 Bangladesh J. Plant Taxon. 18(1): 65-67, 2011 (June)